Experimental Study of the Effect of the Expansion Segment Geometry on the Atomization of a Plain-Jet Airblast Atomizer - Yi Jin; Kanghong Yao; Xiaomin He; Kai Zhang; Yunbiao Wang (International Journal of Aerospace Engineering)
In this paper, the idea of adding an expansion segment over traditional airblast atomizer is proposed to improve the spray performance. According to the systematic experiments, the Sauter mean diameter, the droplet size distribution, and the droplet axial mean velocity were obtained to evaluate the spray performance. The correlations between spray performance and four geometrical parameters of the expansion segment which include the length, the angle, the throat area, and position of liquid jet are considered. The atomizer operates at atmospheric pressure and temperature, and the air liquid ratio range is from 0.48 to 2.85. The data of the results were measured by Phase Doppler Particle Analyzer. The results show that more uniform droplet size distribution can be achieved with the addition of expansion segment, and the droplet size distribution factor q of the case adding the expansion segment is 52.8% bigger than that of the case with no expansion segment. q increases as the length and angle of expansion segment increase. The Sauter mean diameter can be reduced by either reducing the length or angle of expansion segment. As for droplet velocity, it is determined that the droplet velocity increases along the radial direction, which is noteworthy because opposite trend is reported for traditional plain-jet atomizers. With an increase of the length, angle, and throat area of the expansion segment, the droplet axial velocity decays.